Development of millimetric heterogeneous catalyst for biodiesel production - Md. Aminul Islam (2011)
Biodiesel is a renewable, biodegradable and nontoxic fuel. Biodiesel production using various types of heterogeneous metal oxide catalysts has been studied in the past. However, most of these catalysts have been prepared in the form of powders with size ranging from nano- to micrometer. The small particle size may offer high catalytic activity but it gives rise to several problems such as high pressure drops, poor mass/heat transfer, poor contact efficiency and difficulties in handling and separation. Until now, there has been limited work to prepare alkali metal based catalyst in macroscopic form to catalyze the transesterification reaction for biodiesel production. The aim of this work was to develop a heterogeneous catalyst in the form of milimetric spherical beads and to evaluate its performance in biodiesel production in terms of biodiesel yield and catalyst reusability. Preliminary studies involved synthesis of the beads from commercial boehmite powders by the sol-gel method using two different approaches: integrated gelling process and oil-drop granulation process. The gelled beads were then calcined to produce the γ-Al2O3 support beads. It was found that the beads produced by the oil-drop granulation process had higher mechanical strength, thus the process was used for bead production in subsequent works. The γ-Al2O3 support beads were activated by impregnating with aqueous solution of KF NaNO3 and KI, as catalyst. The surface properties of the supported catalysts were analyzed using BET and the basicity properties, evaluated in terms of number and strength of basic sites, were analyzed using CO2-TPD. Bead morphology was studied using SEM. The supported catalysts were used in transesterification reaction with methanol at 60 oC in batch process. The composition of biodiesel was evaluated by the gas chromatography method and the effects of catalyst properties, reaction time, molar ratio of methanol to oil, catalyst loading on biodiesel yield were studied. The reusability of the catalyst was also determined and the leachate of catalyst into the reaction product was verified by XRF. Results show that boehmite was transformed to γ-Al2O3 at 800 oC where crystalline structure was formed, as verified by XRD. The highest FAME yield obtained from KI/γ-Al2O3 catalyst was 98% after 4 h of reaction time at 60 oC and the yield was found to directly correspond to the catalyst basicity. It can be correlated with their generation of K2O, KAlO2 for KI/γ-Al2O3 catalyst as evident from XRD which were possibly the main active sites for the transesterification reaction. Similarly, the activity of KF/Al2O3 catalysts was remarkably improved when the catalysts loading were 0.30g (gCat/gγ-Al2O3) for NaNO3/γ-Al2O3 and 0.24g (gCat/gγ- Al2O3) for KF/γ-Al2O3. The high activity towards the transesterification reaction corresponds to the generation of Na2O, NaAlO2 on NaNO3/γ-Al2O3 catalyst, K2O, KAlF4 on KF/γ-Al2O3 catalyst. The high FAME yield could also be attributed to the mesoporous characteristic of the catalyst with pore diameter of 7-9 nm since the smaller triglycerides molecules could diffuse into the catalyst. Moreover, the catalyst exhibited good operational stability with biodiesel yield of 79% after 11 cycles of successive reuse. In conclusion, a heterogeneous catalyst in the form of milimetric spherical beads with potential application in biodiesel production has been developed.